2016
DOI: 10.1038/srep31521
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and responsive gene expression of Sogatella furcifera under extreme temperature stresses are altered by its vectored plant virus

Abstract: Southern rice black-streaked dwarf virus (SRBSDV), a newly emerged fijivirus causing great loss to rice production in eastern and southeastern Asian countries in recent years, is efficiently transmitted by a rice pest, white-backed planthopper (WBPH, Sogatella furcifera) in a persistent, circulative propagative manner and can be considered as an insect virus. In this study, SRBSDV infection in WBPH was found to increase the vector’s death rate under extreme cold stress but improve its survival rate under extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 53 publications
0
35
0
1
Order By: Relevance
“…These studies in comparative genomics also support the extremely low diversity of populations of Rhizophora and other mangrove species, revealing an evolutionary future threatened by the extreme conditions of intertidal zones. The investigation of genomic data is essential to the elucidation of the history and evolutionary mechanisms of adaptation that occur in parallel in each mangrove population ( Xu et al, 2016 ). Despite the extensive presence of mangroves on tropical coasts, the lack of genetic diversity coupled with changes in sea levels make this ecosystem one of those most influenced by climate change in the current century ( Loarie et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies in comparative genomics also support the extremely low diversity of populations of Rhizophora and other mangrove species, revealing an evolutionary future threatened by the extreme conditions of intertidal zones. The investigation of genomic data is essential to the elucidation of the history and evolutionary mechanisms of adaptation that occur in parallel in each mangrove population ( Xu et al, 2016 ). Despite the extensive presence of mangroves on tropical coasts, the lack of genetic diversity coupled with changes in sea levels make this ecosystem one of those most influenced by climate change in the current century ( Loarie et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…At 12, 24, 36, and 48 h after extreme temperature treatment, compared to the virus-free insects, the SRBSDV-infected WBPH had significantly higher death rates after cold treatment, but significantly lower death rates under heat stress. These results indicate that SRBSDV infection in S. furcifera can increase the vector’s death rate under extreme cold stress but improve its survival rate under extreme heat stress [ 17 ]. Through comparative transcriptome analysis, different gene regulation patterns in WBPH under viral and/or temperature stresses were examined, and many genes involved in metabolism were found to be regulated by the stresses [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The P8 and P10 are putative minor core protein and major outer capsid protein, respectively [ 31 , 33 , 34 ]. Previous studies revealed that SRBSDV infection may regulate the expression of a bunch of rice miRNAs [ 42 ] and some of the RNAi-related genes in WBPH under different temporal conditions, suggesting interactions of the virus and host silencing pathways [ 43 ]. It has been demonstrated that the core component Dicer-2 of siRNA pathway has decisive influences on SRBSDV accumulation and dissemination in insect and vector competence [ 44 ].…”
Section: Introductionmentioning
confidence: 99%